Pemberian Hak Narapidana Lanjut Usia dalam Pemenuhan Hak Kesehatan Di Lembaga Pemasyarakatan - Febrianti, Devi Ayu; Subroto, Mitro (Jurnal Panorama Hukum, 2021)
This study aims to explain the granting of the rights of elderly prisoners in the fulfillment of health rights, the obstacles of the Correctional Institution in fulfilling the rights of elderly prisoners in the health sector and the efforts made by the correctional institutions in dealing with the inhibiting factors in the process of granting these rights. This study applies a descriptive qualitative methodology, the writing aims to provide an understanding of the problems, symptoms, facts, reality, and events that occur. Through in-depth and extensive discussion, it is hoped that the reader will understand the contents of this paper and gain a new understanding. The results obtained indicate that the implementation of the granting of the rights of elderly prisoners in the fulfillment of health rights in prisons has not run optimally, because there are still obstacles experienced. Prison efforts in facing obstacles, so that the implementation of the granting of the rights of elderly prisoners in the fulfillment of health rights. It is hoped that the efforts carried out can resolve obstacles in fulfilling the health rights of elderly prisoners which are carried out as optimally as possible so that there are no deviations in the granting of these rights.